Patterns in community assemblage and species richness of small mammals across an altitudinal gradient in semi-arid Patagonia, Argentina - Andrade, Analia (2014)
This is the first study that explored the altitudinal gradient in Argentine Patagonia. The purpose of this study was to document the effects produced by altitudinal gradients in the arid lands on the community composition, abundance, and species richness of small mammals. Four hypotheses of factors that influence the patterns of diversity proposed for mountain regions were assessed for Patagonian arid lands: reduction in the effective area, changes in biotic and abiotic parameters, isolation of montane communities and feedback between zonal communities. The study was carried out in the Somuncurá Protected Natural Area (500-1600 m a.s.l.), a basaltic plateau from northern Extrandean Patagonia. Mammals were sampled along altitudinal and vegetation gradients. With at least 20 small mammal species, Somuncurá is the place with the uppermost species richness in Patagonia. Small mammal abundance and species richness peaked at intermediate levels (750-1000 m a.s.l.), following a hump-shaped pattern. Temperature is the main factor to the structuring of small mammal communities in the arid lands and is the reason why height and latitude have a similar effect in the species composition. The same spatial pattern can be tracked throughout past climatic changes. Somuncurá should be considered at a higher priority level for conservation.